Cow behaviour and milk yield during different categories temperature-humidity indices - Borshch, Oleksandr. O (2024)
The goal of this investigation was to study the influence of different values of Temperature-Humidity index (THI) on the duration of lying down and feed consumption, productivity, and heat production by dairy cows in two variants of feedlots (with and without shelters). The study was conducted from February 2007 to early August 2021 in the central part of Ukraine (Kyiv region) in different periods of THI. This index was divided into three categories: 1) 66–71: normal (14 days); 2) 72–79: alert (11 days); 3) >80: dangerous (9 days). Two variants of feedlots were selected: Open feedlot with shelters and open feedlot without shelters. The largest increase in values of THI affecting the cows was observed in open feedlots without shelters. There, in alert and danger periods duration of feed consumption decreased by 8.0 and 23.1 min, lying down by 17 and 38 min, productivity by 2.3 kg (or 8.77%) and 3.6 kg (or 13.74%), energy consumption by 4.7 and 9.6 MJ, respectively, in comparison to normal period.